(1.8X+0)-(1.4X+0.6)=

Simple and best practice solution for (1.8X+0)-(1.4X+0.6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1.8X+0)-(1.4X+0.6)= equation:


Simplifying
(1.8X + 0) + -1(1.4X + 0.6) = 0

Reorder the terms:
(0 + 1.8X) + -1(1.4X + 0.6) = 0
Remove the zero:
(1.8X) + -1(1.4X + 0.6) = 0
(1.8X) + -1(1.4X + 0.6) = 0

Reorder the terms:
(1.8X) + -1(0.6 + 1.4X) = 0
(1.8X) + (0.6 * -1 + 1.4X * -1) = 0
(1.8X) + (-0.6 + -1.4X) = 0

Reorder the terms:
-0.6 + (1.8X) + -1.4X = 0

Combine like terms: (1.8X) + -1.4X = 0.4X
-0.6 + 0.4X = 0

Solving
-0.6 + 0.4X = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '0.6' to each side of the equation.
-0.6 + 0.6 + 0.4X = 0 + 0.6

Combine like terms: -0.6 + 0.6 = 0.0
0.0 + 0.4X = 0 + 0.6
0.4X = 0 + 0.6

Combine like terms: 0 + 0.6 = 0.6
0.4X = 0.6

Divide each side by '0.4'.
X = 1.5

Simplifying
X = 1.5

See similar equations:

| 2(x+4)-126=0 | | 3+y=10+3 | | m^2+m+.25=0 | | p+12=24 | | (5-4x)(x-5)=0 | | 12x^2-52x+48=0 | | ln(11x-7)=0 | | 3y-8y=12 | | 6x+5=54-x | | 0.2x+0.01=0.2y | | 20%-39.99= | | 7-9x+10+5x+5x-3=9+2*4 | | 2x-3=1.4 | | -4x*x-4x= | | 1/7(r-49)=6/7 | | 15x^5-21x^4-18x^3=0 | | -12y+7=-13y+1 | | 32/8-23/4= | | 2x+6+3x=x+4x+4.5 | | 7x-1=1+10x | | 4x+4=9x+3-5x+1 | | 3xXx=30 | | 6+77x=33x+18 | | 10x+36-38x= | | 1/8(r-56)=7/8 | | -4+2x=-16+11x | | (x+2)(x-1)(x-4)= | | (x+1)(x+0)(x-2)= | | 5x+9=-57-6x | | 4(x-8)+6(5x+10)= | | 1xX^12=1.105 | | (x+5)(2x-1)(x-2)= |

Equations solver categories